Le possédé de Gérasa (Marc 5,1-20) Quand l'intrigue est théologie - Fabre, Jean-Philippe 1966- (2017)
Mark narrates the scene of the Gerasene Demoniac in a particularly extended way. The emphatic description of the obstacles overcome by Jesus is not only a matter of Mark’s colorful style. The plot’s complexity hides a very subtle theology concerning the Gentile mission. The two-stage narrative construction reveals Jesus’ project: after having showed his power over evil forces, Jesus plans the announcement of this power by the Gentiles. Thus, a plot of revelation appears behind the plot of resolution, showing many angles of the universal Gospel diffusion: its obstructions, its necessity, its legitimacy, its time limits, its actors.
Keywords: Bible. Mark 1-9; Bible. Mark -- Criticism, Literary; Gentiles in the New Testament; Healing of the Gerasene demoniac (Miracle)